Neurogranin as a predictor of memory and executive function decline in MCI patients. (6th March 2018) - Headley, Alison; De Leon-Benedetti, Andres; Dong, Chuanhui; Levin, Bonnie; Loewenstein, David; Camargo, Christian; Rundek, Tatjana; Zetterberg, Henrik; Blennow, Kaj; Wright, Clinton B.; Sun, Xiaoyan
Abstract : Objective: To determine whether high CSF levels of neurogranin (Ng) predict longitudinal decline in memory and executive function during early-stage Alzheimer disease (AD). Methods: Baseline levels of CSF Ng were studied in relation to cross-sectional and longitudinal cognitive performance over 8 years. Data were obtained from the Alzheimer's Disease Neuroimaging Initiative database, and participants with normal cognition (n = 111) and mild cognitive impairment (MCI) (n = 193) were included. Results: High levels of CSF Ng were associated with poor baseline memory scores (β = −0.21, p < 0.0001). CSF Ng predicted both memory and executive function decline over time (β = −0.0313, p = 0.0068 and β = −0.0346, p = 0.0169, respectively) independently of age, sex, education, and APOE ε4 status. When the rate of decline by tertiles was examined, CSF Ng was a level-dependent predictor of memory function, whereby the group with highest levels of Ng showed the fastest rates of decline in both memory and executive function. When examined separately, elevated Ng was associated with cognitive decline in participants with MCI but not in those with normal cognition. The levels of CSF Ng were not associated with cognitive measures when tau and amyloid 42 (Aβ42 ) were controlled for in these analyses. Conclusions: High CSF Ng associates with poor memory scores in participants with MCI cross-sectionally and with poor memory and executive function longitudinally. The association of Ng with cognitive measures disappears when tau and Aβ42 are included in the statistical models. Our findings suggest that CSF Ng may serve as a biomarker of cognition. Synaptic dysfunction contributes to cognitive impairment in early-stage AD.